2017
DOI: 10.5005/jp-journals-10035-1074
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction in Tertiary Private Hospitals in Najran, Kingdom of Saudi Arabia

Abstract: Aim: This study is aimed to assess the level of satisfaction of patients in tertiary private hospitals in Najran, Kingdom of Saudi Arabia. Materials and methods:This study used descriptive crosssectional design through a survey questionnaire.Results: A great majority (57%) of respondents are male. Almost half (46.7%) of the respondents are 26 to 35 years old, some (30.3%) are more than 35 years old. The majority (54.5%) of hospitalized patients are married. Some (35.8%) of them reached the secondary level and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
1
0
0
Order By: Relevance
“…We found the study participants were more satisfied with nurse care compare to doctorcare. The result of this study appeared consistent with the study done by the Kingdom of Saudi Arabia (16) while isinconsistent with the study reported by Southern Saudi Arabia (15) . The study discovered that there were no significant differences between patients' satisfaction and age and gender.…”
Section: Discussionsupporting
confidence: 91%
“…We found the study participants were more satisfied with nurse care compare to doctorcare. The result of this study appeared consistent with the study done by the Kingdom of Saudi Arabia (16) while isinconsistent with the study reported by Southern Saudi Arabia (15) . The study discovered that there were no significant differences between patients' satisfaction and age and gender.…”
Section: Discussionsupporting
confidence: 91%
“…In the modern era, it is the right of every patient to demand best possible care in hospitals and it is the duty of hospital staffs to deliver his/her optimum efforts to ensure satisfaction of the patient[ 31 32 ] and its assessment will give an opportunity to find loopholes in the services for future ratification. [ 33 ] It is also an internationally accepted factor which needs to be studied repeatedly for smooth functioning of the health-care systems.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the medical professionals, and the rest of the PHC personnel need to be supportive of the patients, and the patients themselves need to feel respected and comfortable enough to have a good impact, not only on their health, but also on how they think about the PHC. They should be supplied with services of the highest possible quality and a sanitary environment [27,30].…”
Section: Overall Satisfactionmentioning
confidence: 99%